2022
DOI: 10.1186/s12967-022-03787-9
|View full text |Cite
|
Sign up to set email alerts
|

Continuous high-frequency deep brain stimulation of the anterior insula modulates autism-like behavior in a valproic acid-induced rat model

Abstract: Background Until now, the treatment of patients with autism spectrum disorder (ASD) remain a difficult problem. The insula is involved in empathy and sensorimotor integration, which are often impaired in individuals with ASD. Deep brain stimulation, modulating neuronal activity in specific brain circuits, has recently been considered as a promising intervention for neuropsychiatric disorders. Valproic acid (VPA) is a potential teratogenic agent, and prenatal exposure can cause autism-like sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 104 publications
0
2
0
Order By: Relevance
“…As described previously ( Xiao et al, 2022 ), the experimental arena comprised a topless rectangular box (120 cm × 60 cm × 40 cm) divided into three chambers of equal volumes (left, middle, and right). The chambers were connected by two doors (20 cm × 10 cm) on either wall of the middle volume.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As described previously ( Xiao et al, 2022 ), the experimental arena comprised a topless rectangular box (120 cm × 60 cm × 40 cm) divided into three chambers of equal volumes (left, middle, and right). The chambers were connected by two doors (20 cm × 10 cm) on either wall of the middle volume.…”
Section: Methodsmentioning
confidence: 99%
“…As described previously (Xiao et al, 2022), the experimental arena comprised a topless rectangular box (120 cm × 60 cm × 40 cm) divided into three chambers of equal volumes (left, middle, and right). The chambers were connected by two doors In this study, we constructed a schematic of the PTSD model through the SPS procedure in rats, AR or saline administration modality and the four behavioral paradigms of MWM, EPM, OFT, and SIT.…”
Section: Three-chamber Sitmentioning
confidence: 99%
“…MG-BDNF is implicated in learning-dependent neural plasticity [ 29 ] and may modify social circuit formation in brain regions other than the mPFC, even in adulthood [ 62 ]. For example, the high-frequency deep brain stimulation in the anterior insula, which is a well-known brain region regulating social behavior, improves the impairment of sociability and social novelty preference, but not spatial learning abilities and cognitive rigidity, in valproic acid-exposed rats [ 63 ]. Previous studies have also reported that microglia are related to mPFC circuit formation and cognitive maturation in adolescence [ 24 ]; thus, normalizing MG-BDNF after p45–p50 may be sufficient to restore sociability.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence shows that the insula is a critically impaired region in ASD [11,[24][25][26], dysfunction of which could relate to many behavioral and cognitive symptoms of ASD (e.g., mentalizing and empathizing) [8,44,45]. A recent experiment on an autism rat model demonstrated that cognitive impairment and repetitive/stereotypic-like behaviors might be attributable to the dysregulation of synaptic and associated receptor proteins in the insula [46]. Task-based functional meta-analyses demonstrated decreased activation in the insula in ASD during social cognitive and cognitive control [8,10].…”
Section: Discussionmentioning
confidence: 99%